2016
DOI: 10.1515/aiht-2016-67-2727
|View full text |Cite
|
Sign up to set email alerts
|

Levels of pharmaceuticals in Slovene municipal and hospital wastewaters: a preliminary study

Abstract: Pharmaceuticals in wastewater have clearly raised concern and a broad range of analytical methods has been used to assess the risk as accurately as possible. The aim of our study was to measure and compare the concentrations of atorvastatin, bisoprolol, carbamazepine, ciprofloxacin, clofibric acid, diclofenac, fluoxetine, metoprolol, and sertraline in wastewater samples taken from one municipal and one hospital wastewater treatment plant in Slovenia and to predict the potential environmental burden using the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The photolysis effect of UVB irradiation on the ciprofloxacin is approximately 3 folds of that observed with norfloxacin. In this study, UVB-irradiation is used to remove the contaminants of ciprofloxacin as this compound carried a high risk of contamination of the aquatic environment in both municipal and hospital effluent (4). The results of this study are in agreement with a recent study that showed effective removal of ciprofloxacin with UV irradiation (22).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The photolysis effect of UVB irradiation on the ciprofloxacin is approximately 3 folds of that observed with norfloxacin. In this study, UVB-irradiation is used to remove the contaminants of ciprofloxacin as this compound carried a high risk of contamination of the aquatic environment in both municipal and hospital effluent (4). The results of this study are in agreement with a recent study that showed effective removal of ciprofloxacin with UV irradiation (22).…”
Section: Discussionsupporting
confidence: 88%
“…Ciprofloxacin among the fluoroquinolone is the most likely to be present in the wastewater effluent. Hospital wastewater effluent showed higher concentration (1 ng/L -1µg/L) of ciprofloxacin and potentially impacts a high risk of contamination in both municipal and hospital effluent (4). In one study, the concentrations of fluoroquinolones including ofloxacin, levofloxacin, norfloxacin, and ciprofloxacin were detected in high concentrations in the hospital wastewater effluent to reach 12.11 μg/L for norfloxacin and 9.60 μg/L for ciprofloxacin (5).…”
Section: Introductionmentioning
confidence: 99%
“…Municipal wastewaters from domestic and industrial sources can contain a range of different pharmaceuticals and personal care products. Such municipal effluents can be contaminated by the presence of acetaminophen [28]; diclofenac and carbamazepine [29]; ibuprofen, naproxen and triclosan [30]; and hormones [31]. Moreover, wastewater streams were reported to contain not only antibiotics from different classes (β-lactams, sulfonamides, quinolones, tetracyclines, macrolides, etc.…”
Section: Sources Of the Release Of Waste Streams Containing Pharmamentioning
confidence: 99%
“…Nowadays, numerous studies have detected pharmaceuticals in environmental waters in several countries and therefore, concern about their effects on aquatics biota and also on human health has been rapidly growing . Because of the inadequacy of waste water treatment plants in neutralize organic compounds, drugs taken by humans – illicit and not – end their route into sewage, surface, and underground waters .…”
Section: Introductionmentioning
confidence: 99%